Pengaruh Remunerasi dan Disiplin terhadap Peningkatan Kinerja Pegawai melalui Komitmen Pegawai pada Badan Pengawas Pemilu Jawa Timur - Supratikno Supratikno; Rahmat Agus Santoso (Universitas Mataram, 2022)
The purpose of this study is to determine the effect of remuneration and discipline on improving employee performance through employee commitment to the East Java election supervisory body. This research uses a quantitative approach with explanatory research. The data collection technique used in this study is the Google form. Data analysis was carried out through direct and indirect influence tests. This test was carried out using the bootstrapping method using smartPLS 3.0 and looking at the calculation of the total direct effect and indirect effect. The results of this study are in the form of a positive and significant influence of remuneration and discipline on improving employee performance through employee commitment to the East Java election supervisory body. This means that the higher the level of remuneration and discipline, the more employee commitment will increase so that it can improve the performance of East Java election supervisory body employees.